CONTRIBUTION OF SOCIAL ATTITUDE, LEARNING INTEREST, AND TEACHER COMPETENCE TO STUDENT ADAPTABILITY - Gusti Ayu Sri Mahartini; Dewa Bagus Sanjaya; Titi Chandrawati (Indonesian Journal of Educational Development (IJED), 2023)
This study aimed to determine the contribution of social attitude, learning interest, and teacher competence to the adaptability of fifth grade students at SD Semester II Cluster 3, Tabanan District, Tabanan Regency. This research was an ex post-facto study with a population of 137 students. Sampling applied saturated sampling technique. Research data was collected using a questionnaire instrument. Research data were analysed using multiple regression and partial correlation. The results showed that (1) the significant contribution of social attitudes to adaptive skills was 23.50% and the effective contribution was 8.52%; (2) a significant contribution of interest in learning to adapt skills of 32.9% and an effective contribution of 15.60%; (3) the significant contribution of teacher competence to adaptive skills was 37.50% and the effective contribution was 24.97%; and (4) the combination of the contribution of social attitudes, learning interest, and teacher competence to students' adaptive skills was 49.10%.